### Coming Soon

We are in process of building the inventory of good professionals in this category

Got it!

Where do you need ?

3 Followers

Top Contributors

Sarvajeet

Tapas

Ankit

Chandan

Shikha

Mamata

Ram Mohan

Sreedevi

Rajendran

Thousands of experts Tutors, Trainers & other Professionals are available to answer your questions

Showing 1 to 11 of 11
Sort By:
S

Subhajit 3 days ago in  Factorization

how i make a best actor

You can add upto 6 Images

J

Jagabandhu 09/11/2016 in  Factorization

Sarvajeet replied | 19/11/2016

(m+p)*(n+q)

Muraleedharan replied | 20/11/2016

= n (m + p) + q (m +p)
= (m + p) ( n + q)

You can add upto 6 Images

T

Tanya 09/11/2016 in  Factorization

Find the value of x6 + 1 / x6, if x + 1 / x?

Ankit replied | 22/11/2016

2.

You can add upto 6 Images

D

Divya 09/11/2016 in  Factorization

If 4x - 4x - 1 = 24 then (2x)x equals what?

D

Dinnu replied | 03/12/2016

Not defined

You can add upto 6 Images

T

Thomas 09/11/2016 in  Factorization

Factorise: (cube of x) + x - 3 (square of x) - 3?

Shambhavi replied | 07/12/2016

x^3-3x^2+x-3 is the given equation. Taking x^2 as common from the first two terms, we get, x^2(x-3)+1(x-3) , which can be written as, (x^2+1)(x-3). Thus (x^2+1) and (x-3) are the factors of the equation.

You can add upto 6 Images

S

Sharath 09/11/2016 in  Factorization

Simplify: a9 - 64a3 - a6 + 64?

Shikha replied | 22/11/2016

Please see the attachment for full solution. Final factors are (a3-1) (a3-8) (a3+8).

You can add upto 6 Images

S

Shobhitha 09/11/2016 in  Factorization

Prove that: (1 / a3) + (1 / b3) + (1 / c3) = (1 / a + 1 / b + 1/c)3 + 3 / abc?

Shambhavi replied | 07/12/2016

we know that,
a3 + b3 + c3 = (a + b + c)3 -- 3(a + b)(b + c)(c + a)
a + b + c = 0 implies a + b = -- c, b + c = -- a, c + a = -- b.
(1/a)3 + (1/b)3 + (1/c)3
= (1/a + 1/b + 1/c)3 -- 3(1/a + 1/b)(1/b + 1/c)(1/c + 1/a)
= (1/a + 1/b + 1/c)3 -- 3(a+b / ab)(b + c / bc)(c + a / ac)
= (1/a + 1/b + 1/c)3 -- 3(-- c / ab)(-- a / bc)(-- b / ac)
= (1/a + 1/b + 1/c)3...  more»
we know that,
a3 + b3 + c3 = (a + b + c)3 – 3(a + b)(b + c)(c + a)
a + b + c = 0 implies a + b = – c, b + c = – a, c + a = – b.
(1/a)3 + (1/b)3 + (1/c)3
= (1/a + 1/b + 1/c)3 – 3(1/a + 1/b)(1/b + 1/c)(1/c + 1/a)
= (1/a + 1/b + 1/c)3 – 3(a+b / ab)(b + c / bc)(c + a / ac)
= (1/a + 1/b + 1/c)3 – 3(– c / ab)(– a / bc)(– b / ac)
= (1/a + 1/b + 1/c)3 – 3(abc / a2b2c2)
= (1/a + 1/b + 1/c)3 – 3 / abc.
Thus, proved. «less

You can add upto 6 Images

N

Neelima 09/11/2016 in  Factorization

What do you mean by factorization?

Chandan replied | 22/11/2016

Factorisation:- The resolution of an entity into factors such that when multiplied together they give the original entity.

You can add upto 6 Images

A

A 09/11/2016 in  Factorization

What is the value x + 1 / x, if x3 + 1 / x3?

You can add upto 6 Images

S

Sagar 09/11/2016 in  Factorization

Factorize: (3 * a * x) - 2 . b . x + 3 . a. y - 2 . b. y?

You can add upto 6 Images

A

Akash 09/11/2016 in  Factorization

Factorize: a4 + 5a2 + 9?

You can add upto 6 Images

### Looking for Class IX-X Tuition?

Find best Class IX-X Tuition in your locality on UrbanPro.